Question Number 170226 by ali009 last updated on 18/May/22
$${solve}\: \\ $$$$\begin{cases}{{x}+{y}+{z}+{w}=\mathrm{0}}\\{{x}+{y}+{z}+\mathrm{2}{w}=\mathrm{0}}\\{\mathrm{2}{x}+\mathrm{2}{y}+\mathrm{3}{z}+\mathrm{4}{w}=\mathrm{1}}\\{\mathrm{2}{x}+\mathrm{3}{y}+\mathrm{4}{z}+\mathrm{5}{w}=\mathrm{2}}\end{cases} \\ $$$$ \\ $$
Answered by floor(10²Eta[1]) last updated on 18/May/22
$$\Rightarrow\mathrm{x}+\mathrm{y}+\mathrm{z}+\mathrm{w}=\mathrm{x}+\mathrm{y}+\mathrm{z}+\mathrm{2w}\Rightarrow\mathrm{w}=\mathrm{2w}\Rightarrow\mathrm{w}=\mathrm{0} \\ $$$$\Rightarrow\begin{cases}{\mathrm{x}+\mathrm{y}+\mathrm{z}=\mathrm{0}\:\:\:\:\:\:\:\:\:\left(\mathrm{1}\right)}\\{\mathrm{2x}+\mathrm{2y}+\mathrm{3z}=\mathrm{1}\:\left(\mathrm{2}\right)}\\{\mathrm{2x}+\mathrm{3y}+\mathrm{4z}=\mathrm{2}\:\left(\mathrm{3}\right)}\end{cases} \\ $$$$−\mathrm{2}\left(\mathrm{1}\right)+\left(\mathrm{2}\right)\Rightarrow\mathrm{z}=\mathrm{1} \\ $$$$\left(\mathrm{3}\right):\:\mathrm{2x}+\mathrm{3y}=−\mathrm{2} \\ $$$$\left(\mathrm{2}\right):\:\mathrm{2x}+\mathrm{2y}=−\mathrm{2} \\ $$$$\Rightarrow\mathrm{2x}+\mathrm{3y}=\mathrm{2x}+\mathrm{2y}\Rightarrow\mathrm{y}=\mathrm{0} \\ $$$$\therefore\mathrm{x}+\mathrm{y}+\mathrm{z}=\mathrm{0}\Rightarrow\mathrm{x}+\mathrm{0}+\mathrm{1}=\mathrm{0}\Rightarrow\mathrm{x}=−\mathrm{1} \\ $$